Pengabdian Kepada Masyarakat melalui Pelatihan Pemulasaran Jenazah Covid-19 - Yusuf Rifai; Muna Fauziah (Ar-Rihlah: Jurnal Inovasi Pengembangan Pendidikan Islam, 2022)
The theme of the Real Work Lecture (KKN) organized by IAINU Kebumen is "Civil Society Responsible for COVID-19". With this theme, the Kebumen IAINU KKN activities can be used as a way to train the community about COVID-19 prevention. The author designed a special program related to the KKN theme. The program that has been designed is training on the recovery of COVID-19 bodies specifically for women. The purpose of holding training activities is to train women in the process of recovering COVID-19 bodies. Community service activities were carried out at the NU Muslimat Hall in Redisari Village (Kebumen 4 MTs Complex), Rowokele District, Kebumen. The target of the service is Muslimat and fatayat in the Redisari Village area and its surroundings. The activity was carried out on Friday, September 10 2021. The implementation method used was identifying problems related to the disposal of COVID-19 bodies, designing programs, conducting literature studies, observing field conditions, and conducting training on recovering bodies of COVID-19. Based on field observations, the results obtained were that the community, especially Muslimat and fatayat in Redisari Village, had enthusiastically participated in the body retrieval training activities which were held and the implementation went smoothly.